(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study was conducted to describe the current status of physical activity and associated factors among students at several universities in Hanoi and Thai Nguyen in 2024. Methods: A cross-sectional descriptive study was carried out on 1297 students from five universities in Thai Nguyen province and Hanoi city using the IPAQ-LF tool. Results: The proportion of students meeting the WHO physical activity recommendations was 86.7%, of which 74.2% had high physical activity, 12.5% had moderate physical activity, and 13.3% had low physical activity. Factors significantly associated with physical activity level included gender, major field of study, school area, sitting time and sleeping time during the day. Conclusion: Most students achieved the recommended level of physical activity according to WHO guidelines. however, this level is influenced by gender, field of study, school location, and lifestyle habits. It is necessary to strengthen programs that encourage physical activity, reduce prolonged sitting time, and support students in maintaining regular exercise habits.